2005
DOI: 10.1074/jbc.m505035200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Sulfite Oxidase Deficiency

Abstract: Sulfite oxidase deficiency is a lethal genetic disease that results from defects either in the genes encoding proteins involved in molybdenum cofactor biosynthesis or in the sulfite oxidase gene itself. Several point mutations in the sulfite oxidase gene have been identified from patients suffering from this disease worldwide. Although detailed biochemical analyses have been carried out on these mutations, no structural data could be obtained because of problems in crystallizing recombinant human and rat sulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
149
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(160 citation statements)
references
References 27 publications
(36 reference statements)
11
149
0
Order By: Relevance
“…The assignment of residue 6 in the heme domain to glutamine or glutamic acid in the first crystal structure of native chicken SO was incorrect, and has been re-assigned to arginine in the recently reported structure of recombinant chicken SO, based upon sequencing analysis of native chicken SO [24]. The authors could not grow crystals of the recombinant chicken SO encoding the incorrect residue.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The assignment of residue 6 in the heme domain to glutamine or glutamic acid in the first crystal structure of native chicken SO was incorrect, and has been re-assigned to arginine in the recently reported structure of recombinant chicken SO, based upon sequencing analysis of native chicken SO [24]. The authors could not grow crystals of the recombinant chicken SO encoding the incorrect residue.…”
Section: Introductionmentioning
confidence: 92%
“…Significant alterations in the substrate-binding pocket were detected in the structure of the chicken SO R138Q mutant, and a comparison between the wild type and mutant proteins revealed that the active site Arg-450 residue adopts different conformations in the presence and absence of bound sulfate [24]. The size of the binding pocket is thereby considerably reduced, and its position relative to the cofactor is shifted, causing an increase in the distance of the sulfur atom of the bound sulfate to the Mo.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a human perspective, three molybdoenzymes-sulfite oxidase, xanthine oxidase and aldehyde oxidase-are essential for proper health. In the extreme cases where genetic errors prevent the biosynthesis of functional molybdoenzymes, the resultant neurological problems are typically fatal [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%